Structural equation modeling of basic psychological needs and meaningful sports consumption with the mediating role of team attachment and self-esteem - Xuemeng Hao; Ruilin Xu; Panna Yang; Bingyuan Liang (Scientific Reports)
Abstract The interplay between psychological factors and consumer behavior in sports contexts has drawn significant attention; yet, the mechanisms underlying meaningful sports consumption (MSC) remain underexplored. Basic Psychological Needs (BPNs), team attachment, and self-esteem are key constructs that may influence MSC behaviors, particularly in culturally distinct markets such as China. This study investigates how BPNs’ satisfaction drives MSC directly and indirectly through the mediating roles of team attachment and self-esteem. Using Structural Equation Modeling (SEM) and a mixed-methods approach, the study analyzed data from 320 valid responses collected via online and offline surveys. Measurement scales for BPNs, team attachment, self-esteem, and MSC were developed and validated through Confirmatory Factor Analysis (CFA), ensuring reliability and discriminant validity. The findings show that BPNs impact MSC directly and indirectly through team attachment and self-esteem. Team attachment fosters feelings of nationality, pride, and interest in sports-related information, while self-esteem enhances self-confidence and pride. These psychological constructs lead to MSC behaviours such as supporting domestic sports products, attending local games, and purchasing tickets to support local sports development. Satisfying BPNs is essential for promoting meaningful engagement in sports consumption. Team attachment and self-esteem partially mediate this relationship, providing marketers, sports organizations, and policymakers with insights to enhance fan engagement and promote broader participation in sports. This research advances our understanding of the psychological mechanisms underlying sports consumer behavior.